A Review of the Condition of Common Man in the Gupta Period: The Rise and Conquests of the Gupta Empire (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The Gupta Empire was an old Indian empire existing from the mid-to-late 3rd century CE to 590 CE. At the zenith of its, from about 319 to 550 CE, it covered a lot of the Indian subcontinent. This particular time period is known as the Golden Age of India by certain historians. The ruling dynasty of the empire was created by the king Sri Gupta probably the most important rulers of the dynasty had been Chandragupta I, Samudragupta, plus Chandragupta II alias Vikramaditya. The 5th century CE Sanskrit poet Kalidasa credits the Guptas with owning conquered about twenty one kingdoms, both in as well as outside India, which includes the kingdoms of Paraskos, the Hunas, the Kambojas, tribes located in the west as well as east Oxus valleys, Kiratas, the Kinnaras, and some.